2014
DOI: 10.1186/s13052-014-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolidase activity and oxidant–antioxidant status in children with chronic hepatitis B virus infection

Abstract: BackgroundChronic hepatitis B (CHB) is a global health problem that can result in serious complications associated with collagen degradation. Prolidase is a specific imidodipeptidase that plays an important role in the breakdown of collagen. The aim of this study was to investigate prolidase activity and oxidant–antioxidant status in children with CHB.MethodsThis prospective case control study includes 38 patients with CHB, 31 patients with inactive hepatitis B (IHB), and 29 healthy matched control subjects. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…These studies mostly measured MDA as an oxidation marker, which was significantly higher in patients with hepatitis B infection compared to healthy individuals (Table 1); a marker that was positively correlated to alanine aminotransferase (ALT) (23-25, 30, 31, 41), HBV-DNA (23, 32), total and direct bilirubin (28), serum bcl-2 (this study combined hepatitis B and C patients) (47), gamma-glutamyl transpeptidase (GGT) (31), serum iron/ferritin (44), and liver ultrasonography findings (coarse texture) (28) in some studies. Although another study demonstrated a significant increase in the MDA levels of chronic hepatitis B patients, it did not find a significant difference between inactive HBsAg carriers and controls (48).…”
Section: Resultsmentioning
confidence: 99%
“…These studies mostly measured MDA as an oxidation marker, which was significantly higher in patients with hepatitis B infection compared to healthy individuals (Table 1); a marker that was positively correlated to alanine aminotransferase (ALT) (23-25, 30, 31, 41), HBV-DNA (23, 32), total and direct bilirubin (28), serum bcl-2 (this study combined hepatitis B and C patients) (47), gamma-glutamyl transpeptidase (GGT) (31), serum iron/ferritin (44), and liver ultrasonography findings (coarse texture) (28) in some studies. Although another study demonstrated a significant increase in the MDA levels of chronic hepatitis B patients, it did not find a significant difference between inactive HBsAg carriers and controls (48).…”
Section: Resultsmentioning
confidence: 99%
“…Duygu et al 21 showed that prolidase activity and oxidative stress increase in patients with hepatitis C virus (HCV) infection and that the prolidase enzyme and oxidative damage may be associated with the HCV infection becoming chronic. However, Şen et al 22 reported a significant increase in prolidase activity in children with chronic hepatitis.…”
Section: Discussionmentioning
confidence: 97%
“…TAS is used to assess the overall antioxidant status; similarly, TOS is used to estimate the level of oxidants. One of the most important parameters evaluating oxidative stress is oxidative status index (OSI), which provides an objective assessment of the relationship between the antioxidant barrier and the ROS level and is a useful intensity oxidative stress marker .…”
Section: Discussionmentioning
confidence: 99%
“…The level of phenolic and polyphenolic compounds (pPh) was determined by the colorimetric method of Folin‐Ciocalteu's reagent (FCR) . Lipid peroxidation products – malondialdehyde (MDA) – were determined by measuring the content of MDA with thiobarbituric methods (TBARS) according to the Buege and Austa method .The oxidative stress index (OSI) was calculated from the TOS/TAS × 100 formula . The protein concentration was assessed using the bicinchoninic acid method (BCA) (bovine serum albumin as a standard) (Thermo Scientific PIERCE BCA Protein Assay Kit, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%